Simultaneous Determination and Validation of Hydrochlorothiazide & Eprosartan in bulk drug and Marketed Formulation by Rp-Hplc - Patel, Arun (International Journal of Pharmaceutical & Biological Archive, 2017)
Validation of developed and RP HPLC analytical method according to ICH Guidelines. A review ofliterature reveals that no analytical methods are available for these drugs. There are no methods in theliterature for the estimation of drugs in combined dosage forms. Analytical methods have been report forhydrochlorothiazide and eprosartan using RP-HPLC in pharmaceutical dosage form. The development ofsimple and precise reverse phase high performance liquid chromatography of hydrochlorothizide andeprosartan using single method in bulk in bulk drug and market formulation.